Membendung Arus Progresif: Dinamika Intelektualisme Komunitas NU - Rumadi Rumadi (Universitas Islam Negeri Mataram, 2005)
In the last decade, intellectualism dynamics among the nahdliyyîn (the followers of NU) has shown an incredible passion in terms of spreading some progressive Islamic ideas that are prominently motored by the youth NU. Such intellectualism passion, unfortunately, is not positively welcome by most nahdliyyîn that are engaging conservative thought of Islam. That is why many negative responds raise against the movement. The responds in turn strengthen some stigmatization from external-NU groups that are very eager to resist any elements of what is called progressive or liberal Islam. Oppositions against the movement from internal-NU are currently going stronger. The 31st NU Congress in Boyolali has likely become a peak expression and even peak anger of any exponents of conservative NU opposing the progressive exponents. It not only took form into stereotypically rejecting to what called “liberal Islam” ideas but also to anyone engaging liberal-progressive thought. The atmosphere of intellectualism dynamics within NU after its 31st Congress becomes uncomfortable for seedling progressive Islamic ideas. Although it will not exactly put the progressive intellectual movements out but it will simultaneously present harder challenges to them. Above all, the intellectualism dynamics within NU can be considered the struggle between the conservative and progressive groups.